"Belt & Road" international education and cultural exchange in higher education in Malaysia among mainland Chinese students / Chengcheng Yang, Caesar Dealwis and John Francis Noyan - Yang, Chengcheng; Dealwis, Caesar; Noyan, John Francis (2023)
This article is a conceptual review on the One Belt One Road International Education and Cultural Exchange in Higher Education in Malaysia among Mainland Chinese Students. The "Belt & Road" aimed to create the world's largest platform for economic cooperation, including policy, economics, social and cultural cooperation to achieve mutual reciprocity and mutual benefit. In response to the development strategy of OBOR, institutions of higher learning play important roles incultivating talents and enhancing cross-cultural cooperation. Thus, study abroad opportunities could be the best way to give students a worldwide viewpoint